Pemberdayaan Masyarakat melalui Usaha Pengolahan Bandeng di Desa Pliwetan - Isniyatin Faizah; Wiwik Idayati; Tomy Afandi (STIT Al - Ibrohimy Bangkalan, 2025)
This article explores the potential and challenges of developing milkfish-based enterprises in Pliwetan Village, Palang District, Tuban Regency. Local communities adaptively utilize fishpond land in response to climate variability, positioning milkfish as a strategic alternative when salt production is not feasible. Milkfish has emerged as a leading local commodity due to its distinctive flavor, high meat yield, and potential for value-added processing. However, farmers still face limited market access, dependency on middlemen, weak institutional support, and inadequate processing facilities. These constraints result in price fluctuations and low bargaining power. The article highlights the urgency of diversifying distribution channels through cooperatives, digital marketing, and active involvement of women in the value chain. Institutional strengthening and continuous training are essential to foster innovative processed products, enhance production capacity, and expand market access. With integrative strategies, milkfish has the potential to become a foundation for sustainable local economic empowerment and competitiveness at regional and national levels.